Design estratégico aplicado a mídias tradicionais: como o design pode colaborar para reposicionar o rádio no ambiente digital? - Bernardes, Iglenho Burtet (Universidade do Vale do Rio dos Sinos, 2016)
The communication market is currently undergoing a period of instability and uncertainty, where the continuity of paths or innovation in the media business are not very clear. New digital processes constantly redefine sectors, impacting the radio industry and demanding new solutions. It is in this context that this work was developed, trying to evaluate how the strategic design can support the design of the future scenarios for the radio. To achieve this objective, different forms of data collecting were used, giving emphasis on the search for benchmarks (local, national and international) and interviews with radio specialists. Moreover, the present author has more than 20 years of experience in the radio market, which impacted in the making of this dissertation. The developed research had as a result the identification of possible scenarios for the future of the radio, bringing different perspectives of technology, role of audience and role of communicator. The scenarios projected were then utilized as reference to the development of prototypes, as a form of experimenting and learning. The four established scenarios were denominated: Robot Radio, Expanded Radio, Partner Radio and Talk Radio. Among the results, it is important to point out that the design prototypes were applied in a process of specific planning for the radio station Atlântida FM, developing a concept of multiplatform. The present research presents proposals for a transformation of the audience in possible and relevant cultural collaborators.
Keywords: Rádio; Design estratégico; Comunicação; Cenários; Strategic design; Communication; Scenarios; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial